Antimetastatic Properties of Prodigiosin and the BH3-Mimetic Obatoclax (GX15-070) in Melanoma - Margarita Espona-Fiedler; Pilar Manuel-Manresa; Cristina Benítez-García; Pere Fontova; Roberto Quesada; Vanessa Soto-Cerrato; Ricardo Pérez-Tomás (MDPI AG, 2022)
Metastasis is the primary cause of death in cancer patients. Many current chemotherapeutic agents only show cytotoxic, but not antimetastatic properties. This leads to a reduction in tumor size, but allows cancer cells to disseminate, which ultimately causes patient death. Therefore, novel anticancer compounds with both effects need to be developed. In this work, we analyze the antimetastatic properties of prodigiosin and obatoclax (GX15-070), anticancer drugs of the Prodiginines (PGs) family. We studied PGs' effects on cellular adhesion and morphology in the human primary and metastatic melanoma cell lines, SK-MEL-28 and SK-MEL-5, and in the murine melanoma cell line, B16F10A. Cell adhesion sharply decreased in the treated cells, and this was accompanied by a reduction in filopodia protrusions and a significant decrease in the number of focal-adhesion structures. Moreover, cell migration was assessed through the wound-healing assay and cell motility was severely inhibited after 24 h of treatment. To elucidate the molecular mechanisms involved, changes in metastasis-related genes were analyzed through a gene-expression array. Key genes related to cellular invasion, migration and chemoresistance were significantly down-regulated. Finally, an in vivo model of melanoma-induced lung metastasis was established and significant differences in lung tumors were observed in the obatoclax-treated mice. Altogether, these results describe, in depth, PGs' cellular antimetastatic effects and identify in vivo antimetastatic properties of Obatoclax.